Thioredoxin and metallothionein: Homeostasis-related proteins in lip carcinogenesis. (May 2017) - Caldeira, Patrícia C.; Silva, Laíssa S.; Batista, Aline C.; Aguiar, Maria Cássia F.
Highlights: Immunoexpression of Trx and MT is similar in actinic cheilitis and lip mucosa. Lip carcinoma expresses lower Trx and higher MT scores than actinic cheilitis. The strong correlation between Trx and MT in mucosa is not found in actinic cheilitis and carcinoma. The evaluation of the cellular compartment stained showed to be relevant. Abstract: Objective: Thioredoxin (Trx) and metallothionein (MT) are involved in the development of some carcinomas; however, the role of these proteins in labial carcinogenesis has not yet been tested. The aims of the study were to evaluate and to correlate the immunoexpression of Trx and MT in actinic cheilitis, lip squamous cell carcinoma, and normal vermillion lip mucosa. Design: Immunohistochemistry was undertaken for Trx and MT in samples of actinic cheilitis, lip squamous cell carcinoma, and normal lip mucosa. Qualitative and semi-quantitative evaluations were conducted. The proportion of stained cells, intensity of staining, and the cell compartment labeled were evaluated. A quickscore index was also calculated by multiplying the values of extension and intensity of nuclear and cytoplasmic staining, respectively, giving a maximum value of 9. Statistics were performed. Results: A remarkable nuclear Trx staining was seen in normal lip mucosa and cheilitis, not in carcinoma (p < 0.05). Cytoplasmic Trx expression was widely detected in all lesions (p > 0.05). MT was broadly expressed in nuclei and cytoplasm of carcinoma, but not in normal lip mucosa and cheilitis (p < 0.05). Quickscores were in accordance with the qualitative results. Conclusions: The current study showed a different immunopattern of Trx and MT between normal lip mucosa, actinic cheilitis and lip squamous cell carcinoma. The cellular compartment-based analyses evidenced differences that can be related to the proteins function. Considering the relevant roles of these proteins in cellular homeostasis, they seem to have an important role in lip carcinogenesis.